Skewed megakaryopoiesis in human induced pluripotent stem cell‐derived haematopoietic progenitor cells harbouring calreticulin mutations. (9th May 2018) - Takei, Hiraku; Edahiro, Yoko; Mano, Shuichi; Masubuchi, Nami; Mizukami, Yoshihisa; Imai, Misa; Morishita, Soji; Misawa, Kyohei; Ochiai, Tomonori; Tsuneda, Satoshi; Endo, Hiroshi; Nakamura, Sou; et al.
Summary: Somatic mutations in the calreticulin ( CALR ) gene have been found in most patients with JAK2 ‐ and MPL ‐unmutated Philadelphia chromosome‐negative myeloproliferative neoplasms (MPNs). It has recently been shown that mutant CALR constitutively activates the thrombopoietin receptor MPL and, thus, plays a causal role in the development of MPNs. However, the roles of mutant CALR in human haematopoietic cell differentiation remain predominantly elusive. To examine the impact of the 5‐base insertion mutant CALR gene (Ins5) on haematopoietic cell differentiation, we generated induced pluripotent stem cells from an essential thrombocythaemia (ET) patient harbouring a CALR ‐Ins5 mutation and from a healthy individual (WT). Megakaryopoiesis was more prominent in Ins5‐haematopoietic progenitor cells (Ins5‐HPCs) than in WT‐HPCs, implying that the system recapitulates megakaryocytosis observed in the bone marrow of CALR ‐mutant ET patients. Ins5‐HPCs exhibited elevated expression levels of GATA1 and GATA2, suggesting a premature commitment to megakaryocytic differentiation in progenitor cells. We also demonstrated that 3‐hydroxy anagrelide markedly perturbed megakaryopoiesis, but not erythropoiesis. Collectively, we established an in vitro model system that recapitulates megakaryopoiesis caused by mutant CALR . This system can be used to validate therapeutic compounds for MPN patients harbouring CALR mutations and in detailed studies on mutant CALR in human haematological cell differentiation.